The Case of the EUDIMENSIONS Project - Hajdú, Zoltán; Lux, Gábor; Pálné Kovács, Ilona; Somlyódyné Pfeil, Edit (Discussion Papers, 2012)
EUDIMENSIONS Project had to map and analyse crossborder cooperation and political contact-building between the European Union and neighbouring states, with a special emphasis on the development of civil society, economic interaction and the specific issue of gender in the crossborder relationship network. The authors had been responsible for research on the Hungarian-Ukrainian border area, with a broader outlook on the geopolitical implications of Ukraine’s European integration proc¬esses and political contact-building since independence. They considered the historical, cultural, demographic, ethnic, economic and legal as¬pects of crossborder relationships not just with regards to Hungarian-Ukrainian state relations, but also the specific characteristics of Transcarpathia, a special multicultural region bordered by four new EU member states. The paper descends to the different scales of crossborder relationships (transnational framework of cooperation, NGO sector and CSOs), economic cooperation and civil society, gender issues and social welfare in crossborder cooperation and reviews the local border issues in selected periodicals.